Relationship between the level of knowledge and family support with the level of mother's anxiety during the first stage of labor - Darma, Ika Yulia; Zaimy, Silvi; Hayu, Ramah; Idaman, Meldafia (PT. Riset Press International, 2024)
The level of anxiety in mothers giving birth becomes arrhythmic in the birth experience and can have a long-term impact on the well-being of the mother and baby. This study aims to determine the relationship between the level of knowledge and family support and the level of maternal anxiety during the first stage of labor. Descriptive analytical research type with cross sectional emphasis with a total sample of 31 primigravida mothers in the first stage of labor. The results showed most respondents had a moderate level of anxiety (48.9%), most respondents (77.4%) had a low level of knowledge and most respondents (58.1%) had good family support. The chi square statistical test shows that there is a significant relationship between the level of knowledge and family support and the anxiety level of mothers in the first stage of labor with p values ​​of 0.046 and 0.006 (p value < 0.05), respectively. The level of knowledge and family support is related to the level of anxiety of mothers in the 1st stage of labor.